Clinical and genetic analysis of Christianson syndrome caused by variant of SLC9A6: case report and literature review - Dong, Yan; Lian, Ruofei; Jin, Liang; Zhao, Shichao; Tao, Wenpeng; Wang, Lijun; Li, Mengchun; Jia, Tianming; Chen, Xuejing; Cao, Shushi (Frontiers in Neurology, 2023)
Background: Intellectual disability, X-linked syndromic, Christianson type (MRXSCH, OMIM: 300243)—also known as Christianson syndrome (CS)—is characterized by microcephaly, epilepsy, ataxia, and absence of verbal language ability and is attributed to mutations in the solute carrier family 9 member A6 (SLC9A6) gene. Methods: We report a case of a boy aged 1 year and 3 months diagnosed with CS in our department. The genetic etiology was determined by whole-exome sequencing (WES), and minigene splicing assay was used to verify whether the mutation affect mRNA splicing. A literature review was conducted of cases of CS, and the clinical and genetic features were summarized. Results: The main clinical manifestations of the patient were seizures, developmental regression, and exceptional facial features. WES revealed a de novo splice variant in intron 11 (c.1366+1G>C) of the SLC9A6 gene. The mutation produced two abnormal mRNA products as verified by minigene splicing assay, resulting in amino acid shifts to form truncated proteins. A total of 95 CS cases were identified in the literature with diverse symptoms, mainly delayed intellectual development (95/95, 100.00%), epilepsy (87/88, 98.86%), absent verbal language (75/83, 90.36%) and other manifestations. At least 50 different pathogenic variants of the SLC9A6 gene have been identified with the highest frequency observed in exon 12. Conclusion: Our patient is the first case of the c.1366+1G>C variant of SLC9A6 in Christianson syndrome. The summary of known cases can serve as a reference for analyzing the mutation spectrum and pathogenesis of CS.